Universal rights, systemic violations, and cultural relativism in Morocco - Glacier, Osire; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2013)
Are universal rights bound to colonialism? Are they culturally imperialistic? By juxtaposing Morocco's practice of torture with its discourse of cultural relativism, this study links popular resistance to universal rights to a deliberate politics that delegitimizes those very same rights, requiring a new, more inclusive system of universalism.
Keywords: Political science; Political theory; World politics; International relations; Politics and war; Human rights; Political Science and International Relations; Political Science; Human Rights; Political Theory; Military and Defence Studies; Political History; International Relations